Successful treatment of recurrent unresectable squamous cell carcinoma of the head and neck using pembrolizumab - A. M. Mudunov; I. М. Gelfand; О. D. Ryzhova; A. A. Akhundov; М. N. Narimanov; A. V. Ignatova (Опухоли головы и шеи)
The study objective is to report a case of successful treatment of recurrent unresectable squamous cell carcinoma of the head and neck using pembrolizumab (selective inhibitor, preventing the interaction between the programmed death receptor 1 (PD1) and its ligands PD-L1 and PD-L2).Materials and methods. A 72-year-old male patient was admitted to the Clinic of Head and Neck Tumors, N.N. Blokhin Russian Cancer Research Center with the following diagnosis: primary metachronous malignant tumors: 1) oropharyngeal cancer T2N3M0 (after chemoradiotherapy, no relapse or metastases), 2) skin cancer of the left ear (T2N0M0,  stage II, after combination treatment); relapse. After multiple surgeries for repeated relapses and external beam radiotherapy in March 2017, the patient was found to have new metastatic lesions in the retropharyngeal lymph nodes and paravertebral soft tissues of the neck (left side). The tumor was considered unresectable. The patient had high level of PD-L1 expression in the tumor (50 %), therefore, it was decided to initiate treatment with PD-1 inhibitors. The patient received pembrolizumab (keytruda) 200 mg once every three weeks (7 courses).Results. Positron emission tomography performed in February 2018 demonstrated no increased uptake of radiopharmaceutical in the retropharyngeal lymph nodes and paravertebral soft tissues of the neck, which were earlier affected. Since that time, the patient demonstrates sustained remission without any therapy.Conclusion. This case not only shows high efficacy of PD-1 inhibitors for aggressive recurrent head and neck squamous cell carcinoma, but also opens new opportunities for the treatment of weakened patients after chemotherapy and radiation exposure.